(untitled) (Nexus International Journal of Science and Education, 2024)
The study unfolded the relationship between 120 kinder teachers and food competence practices in early childhood health and nutrition in Governor Generoso South District, Davao Oriental Schools Division. The study used a non-experimental descriptive-correlational research design, where it utilized an adapted survey instrument to gather responses. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that the extent of food competence practices in terms of nutrition knowledge and food safety and hygiene were oftentimes manifested; portion control and mindful eating, healthy food choices, and meal planning and preparation were moderately extensive, while the extent of early childhood health and nutrition in terms of allergen management, mealtime practices, and oral health were moderately extensive. Wellness education was sometimes manifested was extensive. There was a significant correlation between food competence practices and early childhood health and nutrition. Domains of food competence significantly influenced early childhood health and nutrition. Future research may explore the development of evidence-based guidelines and interventions for promoting food competence in early childhood education, considering variations in cultural contexts, socioeconomic factors, and educational approaches.